Balancing Trust and Anxiety in a Culture of Fear - Jayde Cahir (SAGE Open, 2013)
To date, there is no empirical research on the risk perceptions of Sydneysiders following the Cronulla riots nor are there any connections made between risk perceptions and ontological security in the mobile communication literature. This article addresses this gap by exploring the risk perceptions of individuals in the wake of these riots, specifically, their reactions to the new surveillance measures and policing of text messaging. This qualitative study uses empirical data collected from 30 one-on-one interviews conducted 12 to 16 months after the riots. To provide a theoretical framework for these risk perceptions Anthony Giddens’ notion of ontological security, the inner balance between trust and anxiety is used. The data analysis shows that while individuals risk perceptions are complex and contradictory, they use a range of methods to create a balance between trust and anxiety. This article argues that to manage fear in a present or perceived threat, individuals are disposed to mediate any actual or perceived risks by bracketing out anxieties to manage their everyday lives.